Analisis Kelayakan Harga Tenaga Listrik PLTS dengan Metode Life Cycle Cost dan LCOE - Vetty Kartikasari; Agus Yudi Asmoro; Aang Fajar Passa Putra; Digitha Oktaviani Putri; Ika Anggraeni Khusnul Khotimah (Universitas Merdeka Malang, 2024)
Abstract The plan to develop PLTS with a capacity of 50Mwp in Galang Batang SEZ is a form of commitment of the wilus holder to the mandate of Presidential Regulation 112 of 2022 in order to achieve the 23% EBT mix target in 2025. In accordance with the RUPTL document of the owner of the area in 2024-2033, which plans the development of power plants to be cooperated with IPP business entities. So that a techno-economic study is needed to provide an overview of project life cycle costs (LCC), electricity production costs, electricity selling prices and financial feasibility. From the results of the calculation, the Life Cycle Cost (LCC) value obtained in the present value of Rp. 587,672,449,561 and energy production during the project period in PV is 576,918 Mwh so that the resulting cost of electricity production calculated by the LCOE method is Rp. 1,018.64 / kwh or 6.37 cUsD. The scenario of the selling price of electricity with a 10% margin gives a positive NPV result of Rp. 34,590 billion; an IRR value of 10.58% above the WACC of 9.69% and a payback period of 8 years and 9 months. So that the development of PLTS in Galang Batang SEZ by IPP business entities is feasible to be realized.Abstrak Rencana pengembangan PLTS berkapasitas 50Mwp di KEK Galang Batang merupakan bentuk komitment pemegang wilus terhadap amanat perpres 112 tahun 2022 dalam rangka mencapai target bauran EBT 23% di tahun 2025. Sesuai dengan dokumen RUPTL pemilik wilus kawasan tahun 2024-2033 yang merencanakan pengembangan pembangkit untuk dikerjasamakan dengan badan usaha IPP. Sehingga diperlukan suatu kajian tekno ekonomi untuk memberikan gambaran terkait biaya siklus hidup proyek (LCC) , biaya produksi tenaga listrik , harga jual tenaga listrik dan kelayakan finansial nya. Dari hasil perhitungan, diperoleh nilai Life Cycle Cost (LCC) yang di present value kan sebesar Rp 587.672.449.561 dan produksi energi selama periode proyek yang di PV kan sebesar 576.918 Mwh sehingga yang menghasilkan biaya produksi tenaga listrik yang dihitung dengan metode LCOE sebesar Rp. 1.018,64/kwh atau 6,37 cUsD. Skenario harga jual tenaga listrik dengan margin 10% memberikan hasil NPV positif Rp. 34,590 Miliar; nilai IRR 10,58% diatas WACC 9,69% dan pengembalian /payback period 8 tahun 9 bulan. Sehingga pengembangan PLTS di KEK Galang Batang oleh badan usaha IPP layak untuk direalisasikan.